10-Minute of the Rest Interval as the Best Strategy to Pre-Activation on Bench Press Performance Between Groups with Different Levels of Muscle Strength: A Cross-Sectional Study - Alberto Sá Filho; Silvio Roberto Barsanulfo; Alan Bastos; Pedro Augusto Inacio; Fábio Luiz Cahuê; Júlio Brugnara Mello; Ercole Rubini; Marcelo Sales (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study aimed to compare the effect of pre-activation (PA) at different rest intervals (RI) on strength endurance performance in multiple sets of bench press (BP) and among groups with different levels of muscle strength. Method: After body composition measurements and two familiarization sessions, 30 men underwent a bench press one-repetition maximum (1RM) test. Subsequently, five sessions with intervals ranging from 48 to 72 hours, differing only in experimental conditions, were conducted. In all sessions, participants performed the maximum number of repetitions with 85% of 1RM across three sets. In four sessions, the first set served as pre-activation, involving a single set of 1RM. These sessions varied only in the RI between pre-activation (1x1RM) and the main activity, comprising 3 sets of maximum repetitions with a load of 85% of 1RM, with RIs of 5, 10, 15, and 20 minutes. One session served as a control with no preceding activity. Results: the volume load increased significantly at the 10-minute RI compared to the control, 15 and 20 minutes (p=0.009, p=0.003, and p<0.001, respectively). Performance (number of repetitions) improved at the 10-minute RI compared to the control, 15 and 20 minutes in the first set, as well as at the 15- and 20-minute RI in the second set, and the control, 15- and 20-minutes RI in the third set (p<0.05). Conclusion: 10 minutes of interval appears to be the ideal PA strategy to be adopted to improve strength endurance performance in BP.